Description of three new species of automeris hübner, 1819 from colombia and brazil (Lepidoptera, saturniidae, hemileucinae) (2021)
The Saturniidae is one of the most emblematic families of moths, comprising nearly 3000 species distributed globally. In this study, DNA barcode analysis and comparative morphology were combined to describe three new species within the genus Automeris, which is the most diverse genus in the family. Automeris llaneros Decaëns, Rougerie & Bonilla, sp. nov., Automeris mineros Decaëns, Rougerie & Bonilla, sp. nov., and Automeris belemensis Decaëns, Rougerie & Bénéluz, sp. nov. are described from the Colombian Orinoco watershed, the Colombian Eastern Cordillera, and the area of endemism of Belém in the Brazilian Amazonia, respectively. They all belong to the Automeris bilinea (Walker, 1855) species subgroup, which comprises a number of species that are sometimes difficult to distinguish from each other using morphology alone. Here, the description of these three new species is based on significant differences from their closest relatives, either in terms of wing patterns, genitalia, DNA barcodes or a combination of these features.